AFM nano‐mechanical study of the beating profile of hiPSC‐derived cardiomyocytes beating bodies WT and DM1. Issue 10 (10th May 2018) - Dinarelli, S.; Girasole, M.; Spitalieri, P.; Talarico, R.V.; Murdocca, M.; Botta, A.; Novelli, G.; Mango, R.; Sangiuolo, F.; Longo, G.
Abstract: Myotonic Dystrophy type 1 (DM1) is the most common form of muscular dystrophy in adults, characterized by a variety of multisystemic features and associated with cardiac anomalies. Among cardiac phenomena, conduction defects, ventricular arrhythmias, and dilated cardiomyopathy represent the main cause of sudden death in DM1 patients. Patient‐specific induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) represent a powerful in vitro model for molecular, biochemical, and physiological studies of disease in the target cells. Here, we used an Atomic Force Microscope (AFM) to measure the beating profiles of a large number of cells, organized in CM clusters (Beating Bodies, BBs), obtained from wild type (WT) and DM1 patients. We monitored the evolution over time of the frequency and intensity of the beating. We determined the variations between different BBs and over various areas of a single BB, caused by morphological and biomechanical variations. We exploited the AFM tip to apply a controlled force over the BBs, to carefully assess the biomechanical reaction of the different cell clusters over time, both in terms of beating frequency and intensity. Our measurements demonstrated differences between the WT and DM1 clusters highlighting, for the DM1 samples, an instability which was not observed in WT cells. We measured differences in the cellular response to the applied mechanical stimulus in terms of beating synchronicity over time and cell tenacity, which are in good agreement with the cellular behavior in vivo. Overall, the combination of hiPSC‐CMs with AFM characterization can become a new tool to study the collective movements of cell clusters in different conditions and can be extended to the characterization of the BB response to chemical and pharmacological stimuli. Abstract : We exploited the atomic force microscope tip to apply a controlled force over the beating bodies, to assess the biomechanical reaction of the cell clusters over time, both in terms of beating frequency and intensity. By performing a fast fourier transform analysis of the beating profiles, we revealed subtle changes in beating synchronicity, highlighting, for the myotonic dystrophy type 1 samples, an instability that was not observed in wild type cells.